El empleo de los cuentos infantiles en el desarrollo de la creatividad de las niñas y niños de educación inicial nivel II de la unidad educativa colegio militar Lauro Guerrero de la ciudad de Loja periodo 2014-2015 - Díaz Calva, Karla Patricia (2016)
This research is focused on HOW TALES DEVELOP CREATIVITY IN PRE- KINDER STUDENTS, LEVEL II, FROM THE “UNIDAD EDUCATIVA COLEGIO MILITAR LAURO GUERRERO” LOJA, CITY, SCHOOL YEAR 2014-2015. The main objective was determine the influence of tales in the CREATIVITY OF PRE- KINDER students. This research is descriptive and correlational. The methods used were: Inductive-deductive, analytic, descriptive and quantitative. The techniques and instruments worked with a questionnaire, and a creativity valoration test adapted to the Torrance test. The procedures were developed with the Principle authorization. He allowed to the teachers of the institution to work with the kids. To begin with this process, the lesson plan was presented. Also, the selected research instruments were previosly authorizazed to apply on the infants. The population for this research consisted of 22 children that belong to pre-kinder level II, group "B “from “Colegio Militar Lauro Guerrero”. Also, two teachers from level II were part of this research process. The most significant result is that 100 % of teachers said that their aim is to use the children's stories to promote love towards literature. This information was gathered thanks to the instrument and technique applied in this research. As conclusion: The use of techniques such as storytelling, design and collage in the performance of children’s stories in the daily working hours enhance the creative development of the infants. In addition, teachers were recommended to provide adequate spaces that encourage pre-school children to develop love for literature